Prevalence of nephropathy and proximal tubule disorder in human immunodeficiency virus patients under tenofovir therapy - Foroogh Sabzghabaei; Afsaneh Sedighi; Raziyeh Shahi; Vahid Mahmoodi; Jahanbakhsh Khamseh; Neda Rahimian (Journal of Nephropharmacology, 2022)
Introduction: Tenofovir is a common therapy in human immunodeficiency virus (HIV) patients. Objective: This study was carried out to determine the prevalence of nephropathy and proximal tubule disorder in HIV patients under tenofovir therapy. Patients and Methods: In this study, 160 HIV patients under tenofovir therapy were enrolled and the prevalence of nephropathy and proximal tubule disorder was determined and compared. Results: We found, the proximal tubule involvement in 25%, 6.8%, 2.2% and 0% in first year, 2–5 years , 6–10 years and 11–18 years of disease involvement respectively, (P = 0.02). The mean glomerular filtration rate (GFR) diminution was 2.15%, 10.53%, 12.6% and 17.79%, in the first, 2–5, 6–10, and 11–18 years, respectively, again showing a significant difference between years (P = 0.02). Proteinuria was seen in 13.1% of patients. Conclusion: We concluded that GFR diminution and proximal tubule involvement are common and important to be managed in HIV-positive patients under tenofovir therapy, and discontinuation of drug has no positive effect on GFR.